Linguistic Conceptualization of The World in Comparisons (Texas Journal of Philology, Culture and History, 2023)
This article investigates the understanding of the term “conceptual picture of the world” in modern Russian and Uzbek linguistics. Besides that, particular attention is paid to the interpretation of stable comparisons in modern linguistics. Stable comparisons are valued by many linguists as syntactic figures and are an important unit in the study of cognitive features of language. For this reason, stable comparisons have long been the focus of linguists around the world. The article analyzes the research on this topic, which important conclusions are drawn.